Large deformation response of additively-manufactured FCC metamaterials: From octet truss lattices towards continuous shell mesostructures - Bonatti, Colin; Mohr, Dirk (International journal of plasticity, 2017)
Starting with the statically-determinate solid octet truss lattice, the large strain compression response of different metamaterial architectures is analyzed through finite element analysis and compression experiments on additively-manufactured stainless steel specimens. Simulation results clearly demonstrate that for a relative density of 20% the conventional solid octet-truss lattice has a lower specific energy absorption capability than some simple periodic shell structures. The analysis of the closed-packed hollow sphere assembly subject to hydrostatic compression reveals that the constituent hollow spheres initially transform into rhombic dodecahedra, which results in significant strengthening at the macroscopic level. Unlike the octet-truss with solid struts, hollow octet truss structures remain stable for hydrostatic, confined and uniaxial compression at the lowest relative density considered. Its strength, in particular at small plastic strains, is substantially improved when substituting the geometric hollow truss joints for hollow spheres. The continuous shell mesostructures defined by the Hybrid (hollow) Truss-Sphere (HTS) and the hollow octet truss assembly exhibited the highest strength and energy absorption potential at 20% relative density for the high and low strain-hardening materials considered, respectively. Moreover, it is found that the HTS metamaterial exhibits the highest relative Young's and bulk moduli among all four architectures considered. It is also shown computationally that hollow rhombic dodecahedral mesostructures could provide nearly twice the strength and energy absorption of the conventional octet truss. •Found that shell-like mesostructures remain stable at relative densities above 20%.•Their specific energy absorption can be more than 60% higher than that of the octet truss lattice.•Confirmed computational results through compression experiments on additively-manufactured porous stainless steel specimens.•Hollow rhombic dodecahedral mesostructures provide nearly twice the strength and energy absorption of the octet truss.